PERLINDUNGAN HUKUM PADA ANAK DI WILAYAH KONFLIK BERSENJATA DI INDONESIA - Saputri, Septiani; Deliana, Evi; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The armed conflict that occurred in Wamena in Papua caused many victims,including children. So the need for special legal protection for children who are in conflictsituations. As in article 60 of Law Number 35 Year 2014 concerning Amendments to LawNumber 23 of 2002 concerning Child Protection, it states: children in an emergency situationas referred to in article 59 paragraph (2) letter a consist of: a. Children who become refugeesb. Children victims of riots; c. Child victims of natural disasters; and d. Children in situationsof armed conflict. Based on the main ideas above, it can be formulated several problems,namely whether the form of criminal acts committed against children in the area of armedconflict in Indonesia and how the legal protection of children from criminal acts in the areaof armed conflict in Indonesia.The writing of this thesis uses the normative legal research method by collectingdata by library research, namely by examining library materials or secondary data in theform of primary legal materials namely related regulations, secondary legal materials namelyrelated documents and tertiary legal materials which is a guide to primary and secondarylegal materials or research on legal systematics. The secondary data that has been compiledare then analyzed using qualitative methods to obtain results, which are forms of protectionfor children in conflict areas, that is, doing things that can accelerate the conducive situationin the field, besides the government in particular, and other supporting elements to furtheroptimize efforts to restore children's health and post traumatic psychological handling inchildren. The conclusion from the results of the study, namely the legal protection of childrenin armed conflict areas in Indonesia who get violence such as murder, sexual harassment orrape is still not working properly, because there are still many children who are victims.Where the rules regarding legal protection of children in conflict areas are still general innature which are civilians. Where the Indonesian government should make special rulesregarding the protection of children in areas of armed conflict. This is the cause of the lack ofjustice obtained by children.Keywords: Legal Protection, Children, in the Area of Armed Conflict